Operational Deflection Shape Extraction from Broadband Events of an Aircraft Component Using 3D-DIC in Magnified Images - Ángel J. Molina-Viedma; Elías López-Alba; Luis Felipe-Sesé; Francisco A. Díaz (Shock and Vibration)
Recently, many works have shown the capabilities of noninterferometric optical techniques, such as digital image correlation, to characterise modal behaviour. They provide a global insight into the structure or component behaviour which implies massive spatial information, unaffordable by traditional sensor instrumentation. Moreover, phase-based motion magnification (PMM) is a methodology which, based on a sequence of images, magnifies a periodic motion encoded in phase time-domain signals of the complex steerable pyramid filters employed to decompose the images. It provides a powerful tool to interpret deformation. However, the interpretation is just qualitative and should be avoided if out-plane motion is recorded as only one camera is employed. To overcome this issue, 3D digital image correlation (3D-DIC) has been linked with PMM to provide measurements from stereoscopic sets of images, providing full-field displacement maps to magnified images. In this work, the combination of PMM and 3D-DIC has been employed to evaluate the modal behaviour of an aircraft cabin under random excitation. The study was focused on the passenger window area due to its significance to the structural integrity as a discontinuity of the peel. Operational deflection shapes at different resonances were characterised by magnifying a single resonance in the spectrum and then measuring with 3D-DIC. These measurements were validated with those obtained in forced normal mode tests. Motion and displacement videos improved the understanding of the identified resonance deformation. Actually, a relevant behaviour was noticed in the window’s frame, a quite narrow area where using traditional sensors would not provide such a detailed 3D information.